PENGARUH PERLAKUAN MIKROGRAVITASI PADA BIJI CABAI RAWIT TERHADAP LAJU PERTUMBUHAN TANAMAN CABAI RAWIT (CAPSICUM FRUTESCENS L.) - Yuni Pramita Utami, Ni Luh; Rupiasih, Ni Nyoman; Supardi, I Wayan (BULETIN FISIKA, 2017)
The study has been done on the effect of microgravity on cayenne pepper seed (Capsicum frutescens L.) on the growth rate and percentage of live of cayenne pepper plant. Microgravity is simulated by 2-D clinostat with the rotation speed of 2.7 rpm (1.22 × 10 -4 g). The microgravity treatments werevariatewith time, known for 12 h (S1), 24 h (S2), and 48 h (S3).The seeds that have been clinorotated were planted in normal gravity environment, 1 g. Plant height and percentage of life measurements were carried out every dayduring the vegetative phase of plant of 0-40 days. The results showed that microgravity treatment on seeds gives positive effect on the growth rate of the cayenne pepper plant.